Field-Based Model for Switched Reluctance Generators in Direct Drive Wind Energy Converters - Lobato, Pedro; Dente, J. A.; Pires, A. J. (My University, 2019)
This work is motivated by the application of Switched Reluctance Generator (SRG) to direct-drive wind turbines and other low speed renewable energy systems. Direct drive energy converters take important benefits from the elimination of the gearbox, which has traditionally been used to interface a slowly prime mover shaft with the generator shaft. Moreover, the actual trend of exploiting the offshore wind resources makes robustness and reliability vital to the economic operation of wind turbines in that specific environment. The proposed field-based model with a triangular approach of the characteristics of flux-linkage makes it easy to incorporate magnetic saturation by introducing some constraints. With a specific aid of finite element analysis, the triangular approach of magnetic characteristics is used to make the comparison of SRG topologies a less time-consuming task. This work underlines dimensional and similarity arguments to extend previous discussions about SRG modeling into a more general context.
Trabalho apresentado em 54th International Universities Power Engineering Conference, 3-6 setembro 2019, Bucareste, Roménia
Keywords: Field-based models; Flux-linkage characteristics; Switched Reluctance Generators